2010
DOI: 10.1371/journal.pone.0014368
|View full text |Cite
|
Sign up to set email alerts
|

So Different, yet So Similar: Meta-Analysis and Policy Modeling of Willingness to Participate in Clinical Trials among Brazilians and Indians

Abstract: BackgroundWith the global expansion of clinical trials and the expectations of the rise of the emerging economies known as BRICs (Brazil, Russia, India and China), the understanding of factors that affect the willingness to participate in clinical trials of patients from those countries assumes a central role in the future of health research.MethodsWe conducted a systematic review and meta-analysis (SRMA) of willingness to participate in clinical trials among Brazilian patients and then we compared it with Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 42 publications
3
38
0
3
Order By: Relevance
“…These results were similar to a recent study, which also demonstrated altruism-related motivations as major reasons for Brazilian patients to participate in clinical research 30. However, among the other groups, the major reason for patients would be access to better healthcare as well as access to treatment alternatives for their diseases, reflecting personal benefits as motivation, which are also described in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…These results were similar to a recent study, which also demonstrated altruism-related motivations as major reasons for Brazilian patients to participate in clinical research 30. However, among the other groups, the major reason for patients would be access to better healthcare as well as access to treatment alternatives for their diseases, reflecting personal benefits as motivation, which are also described in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…For example, studies in a variety of Western settings demonstrate the importance of altruism [24], [25], [44]. Our group's study of Indian subjects found that a sense of altruism was a recurring theme as well [29].…”
Section: Discussionmentioning
confidence: 72%
“…Prior work has also examined factors associated with research participation in emerging-economy cultures such as Brazil and India. Such trials found that personal health benefits offered by the trial and a sense of altruism contributed to research participation, whereas there were a variety of barriers including mistrust of researchers, fear of side effects of the intervention, and inconvenience to the subject [24]–[28]. However, it is well accepted that motivations for research participation vary between patients of different cultural backgrounds [29]–[32].…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been noted in numerous settings of research and across cultures 39 40. Many associate a sense of mistrust to past research misconduct 41.…”
Section: Discussionmentioning
confidence: 78%